Procesowe podejście do badania efektywności - Czakon, Wojciech (Process Approach to Efficiency Measurement, 2005)
The article is focused on the process approach to efficiency measurement. Problems of numerous meanings of the efficiency category, the need of organizations' activity systems identification, and activity based costing usefulness as calculation tool. Efficiency seems to be a research rather than a calculation problem to the decision maker.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 56-63